CONTRIBUTION OF WOMEN ARTISTS TO THE WASH PAINTING TRADITION IN UTTAR PRADESH - Verma, Kirti; Chauhan, Arvind; Tripathi , Saurabh; Singh, Siddharth; Saha, Abhijit; Verma, Robin (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Wash style is an essential and delicate painting tradition in Indian painting, effectively conveying nuances of emotion, light and shadow, and atmosphere through incomplete layers of watercolor. This style holds a special place for its soft color scheme, lyricism, and emotional expression. Uttar Pradesh has been a major center of Indian art traditions, where rich traditions of Mughal, Rajput, and folk painting have developed diverse forms of painting. It is within this cultural landscape that the wash style has firmly established itself and expanded over time. The primary objective of this research paper is to study and analyze the contributions of women artists to the wash style painting tradition in Uttar Pradesh. Through the wash style, women artists have effectively expressed their life experiences, social environment, understanding of nature, and the sensibilities of women's lives. Their paintings clearly demonstrate soft color combinations, nuanced lineage, emotional depth, and a sense of belonging, further enhancing the essence of the style. This study examines the artistic contributions of women artists based on their works and establishes their crucial role in the preservation, development, and dissemination of the Washoe Style. This research is a valuable attempt to understand the Washoe Style tradition from a new perspective.